Role of sludge biochar immobilized multifunctional microbiome in phytoremediation of lead-zinc composite pollution - Zihao Yang; Lijuan Jiang; Xuejun Li; Qiaoling Ji; Mengyuan Wang; Yi Zhang; Yuanlin Cheng; Xuan Zhang; Hui Li; Chongling Feng (Biochar)
Abstract Sludge biochar, as a soil amendment, has demonstrated its capacity to remediate heavy metal-contaminated soil. It is frequently utilized to facilitate phytoremediation or as a microbial carrier in remediation strategies, aiming to enhance overall remediation efficiency. Nonetheless, there exists a knowledge gap regarding the influence of biochar on the migration and accumulation of Pb and Zn within soil-microbe-plant systems, as well as its effects on plant growth conditions and microbial community composition. This study constructed a multifunctional microbiome and evaluated the role of microbiome and biochar in phytoremediation under Pb and Zn stress. Biochar immobilized microbiome (MB) significantly enhanced phytoremediation and showed synergistic effects by improving root phenotypes up to 2.4 times compared to the untreated group (CK). Meanwhile, the MB increased Pb root absorption by 56.9% and Zn aboveground transfer by 30%, and reduced the acid-extractable content of Pb and Zn under high concentrations. In addition, microbial community composition and diversity analyses showed that the bacterial and fungal communities of MB were more stable while multifunctional microbiome reshaped microbial community with boosted abundance of plant growth promoting microorganisms, and fungi of saprotroph and symbiotroph nutritional categories. This study provided a novel phytoremediation approach of castor with the combination of multifunctional microbiome and biochar. Graphical Abstract